(untitled) (American Journal of Islam and Society, 2004)
An Introduction to Islam by David Waines consists of three parts: “Foundations,” “Islamic Teaching and Practice,” and “Islam in the Modern World.” The author begins by characteristically painting the picture of pre- Islamic pagan Arabia on the eve of Islam’s advent. He discusses the role and significance the pre-Islamic Arabs accorded their pantheon of deities, as well as the (largely inherited) moral codes that governed their conduct in tribal society. Waines neatly ties this into what follows, where he discusses the birth of Prophet Muhammad, the event of the Qur’an’s revelation, and the opposition he encountered from his fellow tribesmen in Makkah. This is followed by an analysis of the Qur’an’s significance, its conception of divinity, and the content and importance of the Hadith as a source of guidance for Muslims. The section is rounded off with examinations of such topics as the first period of civil strife (fitnah) after the Prophet’s death and the interesting body of literature devoted to Muslim-Christian polemics in early medieval Islam. The transition from the first part of the book to the second part is rather fluid, for the second part is essentially an elaboration of the themes discussed in the first. With remarkable ease and accuracy, the author elucidates the historical development and main features of Islamic law in both its theory and practice. Returning to his earlier discussion on the Hadith, here he briefly outlines how its corpus came to be collected. Readers unfamiliar with the main theological controversies that confronted Islam in its formative years (e.g., the problem of free will and the status of the grave sinner) will find the section devoted to Islamic theology fairly useful. Waines goes on to explain some of the principle Mu`tazilite and Ash`arite doctrines, and outlines some of the ideas of Neoplatonic Islamic philosophy, albeit through the lenses of al-Ghazali’s famous refutation. Surprisingly, the author does not address any of the major developments in Islamic philosophy post-Ibn Rushd, such as the important work of the Ishraqi (Illuminationist) school (incidentally, the founder of this school, Shihab al-Din Suhrawardi, was a contemporary of Ibn Rushd). The last two chapters are devoted to Sufism and Shi`ism, respectively. Although Waines does misrepresent Ibn al-`Arabi’s metaphysics of Being by calling it a “system” (pp. 153 and 192), on the whole he presents the Islamic mystical tradition in a refreshing and informed manner. His section on Shi`ism is splendid. It is written with considerable care, and he effectively isolates the main themes characteristic of Twelver Shi`ite thought and practice. In the third and longest part of this work, Waines incorporates Ibn Battutah’s travel accounts into the book’s narrative. This works very well, as it gives readers a sense of the diverse and rich cultural patterns that were intricately woven into the fabric of fourteenth-century Islamic civilization. After reading through the section, this present reviewer could not help but marvel at how the observations of a fourteenth-century traveler and legal judge from Tangiers could so effectively contribute to a twenty-first century introductory textbook on Islam. Additionally, Waines takes readers through some of the essential features of the three important “gunpowder” Muslim dynasties, devotes an interesting discussion to the role played by the mosque in a Muslim’s daily life, and outlines some of its different architectural and artistic expressions throughout Islamic history ...